2015
DOI: 10.2515/therapie/2015016
|View full text |Cite
|
Sign up to set email alerts
|

New Methadone Formulation in France: Results from 5 Years of Utilization

Abstract: -Background. In France, methadone has historically been less accessible than buprenorphine. In 2008, a dry formulation (capsule) was introduced into the market, aimed in particular to improve methadone accessibility. Objective. To describe the impact (prevalence of use, patient profiles and compliance with requirements) of the dry methadone formulation in France. Method. A retrospective cohort (from 2008 to 2012) was created from the data of the French General Health Insurance System which covers 80% of the Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In France, where the capsule formulation of MMT recently became available in addition to the syrup formulation, two recent studies showed the potential superiority of the dry (capsule) MMT formulation [ 18 , 26 ]. Boucherie et al (2015) demonstrated that there was a rise in capsule MMT users in a five year period with a corresponding drop in prevalence of individuals using the syrup formulation [ 26 ], and Eiden et al (2013) described 80 % of patients experienced negative side effects from use of the syrup MMT formulation [ 18 ]. In light of the large proportion of MMT patients in our study who reported worse taste and its relation to negative outcomes, consideration of other formulations of methadone including the capsule form, may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In France, where the capsule formulation of MMT recently became available in addition to the syrup formulation, two recent studies showed the potential superiority of the dry (capsule) MMT formulation [ 18 , 26 ]. Boucherie et al (2015) demonstrated that there was a rise in capsule MMT users in a five year period with a corresponding drop in prevalence of individuals using the syrup formulation [ 26 ], and Eiden et al (2013) described 80 % of patients experienced negative side effects from use of the syrup MMT formulation [ 18 ]. In light of the large proportion of MMT patients in our study who reported worse taste and its relation to negative outcomes, consideration of other formulations of methadone including the capsule form, may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…34 In parallel, there was a clear increase in abuse-associated and misuse-associated factors between 2008 and 2018: reports of illegal methadone use quadrupled, the number of capsule injections increased fivefold, and the number of serious cases requiring hospitalization increased by more than tenfold. 34 – 37 …”
Section: Reviewmentioning
confidence: 99%